PENERAPAN METODE MULTIFACTOR EVALUATION PROCESS PADA SISTEM PEMILIHAN SMARTPHONE (Universitas Palangka Raya, 2016)
Now mobile phones are not a luxury but has almost become a primary need for the grasstoots. Everyone has at least one or more mobile phones. In addition to being a means of communication mobile phones can also be used for office work such as editing documents, create presentations, and many more functions of mobile phones today are multitasking and has its own operating system that we often call with smart phones . phones offered from a certain brand with a variety of types that have a variety of specifications. To make decisions in the smartphones there are several criteria that the assessment by the user. By implementing Multifactor Evaluation Process Methods on decision support, and then implemented into a system, which provide an alternative smartphones according to the criteria desired by the user.